Star trek II : the wrath of Khan [videorecording (DVD)] - Meyer, Nicholas, 1945-; Shatner, William; Nimoy, Leonard; Kelley, DeForest, 1920-1999; Doohan, James; Koenig, Walter, 1936-; Takei, George, 1937-; Nichols, Nichelle; Montalbán, Ricardo; Roddenberry, Gene; Alley, Kirstie (Paramount Pictures Corp., 2009)
The Federation Starship U.S.S. Enterprise is on routine training maneuvers when it comes up against Khan, a genetically enhanced conqueror of late 20th century Earth who has escaped his prison and has set his sights on capturing Project Genesis and destroying Kirk.